2018
DOI: 10.1093/labmed/lmy033
|View full text |Cite
|
Sign up to set email alerts
|

Association betweenmiRNA-146aand Polymorphisms of its Target Gene,IRAK1, Regarding Susceptibility to and Clinical Features of Systemic Lupus Erythematous and Multiple Sclerosis

Abstract: Single-nucleotide polymorphisms (SNPs) in microRNA-146a (miRNA-146a) can be associated with the development of immune-system dysfunctions.The aim of this work is to correlate SNPs of miRNA-146a and its target gene, IRAK1, with susceptibility, clinical manifestations, and diseases progression in patients with systemic lupus erythematous (SLE) and multiple sclerosis (MS). Genotyping for miRNA-146a (rs2910164) and its target gene IRAK1 (rs3027898) was performed using real-time polymerase chain reaction (RT-PCR) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…The EDSS score ranges from 0-10 in 0.5-unit increments, with a higher score representing a higher level of disability (23). A value of 6 is a cut-off value, with scores ≥6 meaning a patient who is immobile and requires a walking aid to walk ~100 m with or without rest (15,23). Patients with concurrent autoimmune or inflammatory diseases or malignancies, patients suspected to be drug or alcohol addicts, or pregnant patients were excluded from the present study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The EDSS score ranges from 0-10 in 0.5-unit increments, with a higher score representing a higher level of disability (23). A value of 6 is a cut-off value, with scores ≥6 meaning a patient who is immobile and requires a walking aid to walk ~100 m with or without rest (15,23). Patients with concurrent autoimmune or inflammatory diseases or malignancies, patients suspected to be drug or alcohol addicts, or pregnant patients were excluded from the present study.…”
Section: Methodsmentioning
confidence: 99%
“…The age of onset level was set at 30 years as MS primarily manifests in young adults aged 20-40 years (24) and this age is similar to the mean age of onset in the present study. Patients were also divided into two groups based on the EDSS values; the threshold of severe MS was set as an EDSS score of 6 in accordance with a previous study (15). Finally, patients with MS were divided according to the subtype, RRMS and SPMS (25).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A great number of miR-polymorphisms have been associated with many diseases, including CNS-related disorders [102]. As an example, association between miR-146a and polymorphisms of its target gene, interleukin receptor associated kinase 1 (IRAK1), contributed to the susceptibility of MS patients [103]. Notably, Zhang et al [104] reported that miR-146a promoted remyelination in CNS via IRAK1, and that miRIDIAN miR-146a mimic treatment (by Dharmacon) significantly decreased the level of the protein IRAK1 [104].…”
Section: Potential Role Of Mirna Polymorphisms In Drug Response and Ementioning
confidence: 99%
“…A genetic study on Egyptian population has studied SNPs rs2910164 (MIR146A) and rs3027898 (IRAK1) and its influence to suspect Systemic Lupus Erythematosus (SLE) and MS autoimmune diseases (Labib et al 2019). The study was applied on 80 SLE cases, 70 MS cases and 120 controls.…”
Section: Introductionmentioning
confidence: 99%